Diffuse correlation spectroscopy for non-invasive blood flow measurement. - Toh, Hui Jin. (2011)
Diffuse Correlation Spectroscopy (DCS) is a novel promising technique which adopts the diffusive nature of light propagation in resolving motions of scatterers in the turbid media to initiate non-invasive in-vivo analysis of blood flow. Unlike conventional non-invasive methods, DCS does not involve external contrast agents usage and radiation dose concerns. In addition, DCS has a distinguishing feature of probing deep tissues with high resolution, given its high sensitivity to minute displacements in biological samples. This proficiency makes adequate information about capillary blood flow achievable in the fields of mammography[1]. Hence, the advantage of having high contrast resolutions enables diverse applications of DCS, especially in medical diagnostics such as medical imaging[2-3].